(untitled) (Jurnal Adabiya, 2020)
Dynasty of Saljuk is a group of Turks originating from the tribe Ghuzz. Dynasty of Saljuk attributed to their ancestors named Saljuk ibn Tuqaq (Dukak). Their home country is located in the northern region of the Caspian sea and the Aral Sea and they embraced Islam at the end of the 4th century H / 10M and more to the Sunni school. The development of the Dynasty of Saljuk was aided by the political situation in the Transoksania region. At that time there was a political rivalry between the Dynasty of Samaniyah and the Dynasty of Khani- yyah. In this competition Saljuk tended to help the Dynasty of Samaniyah. When the Dynasty of Samaniyah was defeated by the Dynasty of Ghaznawi, Saljuk declared independence. Thugrul proclaimed the establishment of the Dynasty of Saljuk. In 432 H/1040 AD this dynasty received recognition from the Abbasid Caliphate in Baghdad. At the time of Thugrul Bek’s leadership, in 1055 CE the Saljuks entered Baghdad in the place of the Buwaihi dynasty. Previously Thugrul managed to seize the area of Marwa and Naisabur from Ghaznawi power, Balkh, Jurjan, Tabaristan, Khawarizm, Ray and Isfahan. This year Thugrul Bek also got the title of the Abbasid caliph with Rukh al-Daulah Yamin Amir al-Muminin. Although Baghdad can be controlled, but not used as a center of government. Thugrul Bek chose the city of Naisabur and then the city of Ray as the center of govern- ment. These earlier dynasties broke away, having been conquered by the Saljuq dynasty again recognizing the position of Baghdad. In fact they established the integrity and security of the Abbasids.